1985
DOI: 10.1126/science.2990029
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Induced Delay of Normal Cell Death in the Avian Ciliary Ganglion

Abstract: Repeated administration of morphine in increasing doses delayed normal cell death in the ciliary ganglion of the chick embryo; the effect was completely blocked by naloxone. Survival of spinal motoneurons was not affected. Morphine also inhibited potassium-stimulated synthesis of acetylcholine in ganglion cells cultured with muscle, suggesting that morphine can influence neurotransmission. Morphine's effect on cell death may be due to an inhibition of transmission at the neuromuscular junction, but opiates may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Alternatively, the increases in tumour size could simply have been due to a direct effect of morphine that resulted in enhanced cellular proliferation in the tumours or reduced cell death. Indeed, morphine has been shown to prevent the normal cell death in the ciliary ganglion of the chick embryo, suggesting that in addition to modulating neurotransmission, it and other endogenous opiates may also regulate neurophysiology (22). The concentration of morphine appeared to be important in which effect it caused, as apoptosis in the chick embryo was only disrupted when used at the higher doses, whilst no effect was seen at the lower doses (6).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the increases in tumour size could simply have been due to a direct effect of morphine that resulted in enhanced cellular proliferation in the tumours or reduced cell death. Indeed, morphine has been shown to prevent the normal cell death in the ciliary ganglion of the chick embryo, suggesting that in addition to modulating neurotransmission, it and other endogenous opiates may also regulate neurophysiology (22). The concentration of morphine appeared to be important in which effect it caused, as apoptosis in the chick embryo was only disrupted when used at the higher doses, whilst no effect was seen at the lower doses (6).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, current evidence indicates that depending on the cell type and opioid dosage, opioids can have paradoxicalneuroprotective or neurodegenerative effects (30,59,60). Morphine or Met-enkephalin can inhibit neuronal cell death in the avian ciliary ganglion (59,60). In a cell line transfected with μ opioid receptors, the μ agonist DAMGO ([D-Ala 2 ,N-Me-Phe 4 ,Gly 5 -ol]-enkephalin) activates Akt-induced neuroprotection (70).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 20 years ago, Meriney et al (1985) reported that morphine administered during embryogenesis prevents apoptosis of ciliary ganglion neurons that normally die during the period of synapse formation. They suggested that this effect was mediated through a neurotrophic mechanism or inhibition of neurotransmission (Meriney et al, 1985).…”
Section: Growth-promoting and Protective Effectsmentioning
confidence: 99%
“…They suggested that this effect was mediated through a neurotrophic mechanism or inhibition of neurotransmission (Meriney et al, 1985). Morphine also prevented peroxynitrite-induced apoptosis in primary astrocytes (Kim et al, 2001) and enhanced the proliferation of endothelial cells (Gupta et al, 2002), kidney fibroblasts (Singhal et al, 1998), and adult hippocampal progenitor neurons (Persson et al, 2003).…”
Section: Growth-promoting and Protective Effectsmentioning
confidence: 99%
See 1 more Smart Citation